A 2-hop LoRa Approach Based on Smart and Transparent Relay-Device - Diop, Mamour; Pham, Congduc; Thiare, Ousmane (Springer Nature, Switzerland, 2019)
LoRa is designed for long-range communication where devices are directly connected to the gateway, which removes typically the need of constructing and maintaining a complex multi-hop network. Nonetheless, even with the advantage of penetration of walls, the range may not sometimes be sufficient. This article describes a 2-hop LoRa approach to reduce both packet losses and transmission cost. To that aim, we introduce a smart, transparent and battery-operated relay-devicethat can be added after a deployment campaign to seamlessly provide an extra hop between the remote devices and the gateway. Field tests were conducted to assess relays’ ability to automatically synchronize to the network without advertising their presence.
Recently, Low-Power Wide Area Networks (LPWAN) play a key role in the IoT maturation process. This is a broad term for a variety of technologies enabling power efficient wireless communication over very long distances.
Keywords: LoRa; Low-power IoT; Low-cost IoT; Multihop; Rural area